Translation and validation of stroke impact scale-16 in Urdu for Pakistan - Ahmed, Umair; Hossein Karimi; Syed Amir Gilani; Ashfaq Ahmad (Journal of the Pakistan Medical Association, 2022)
Objective: To translate and validate the Urdu version of stroke impact scale-16 for Pakistani society. Method: The prospective cohort study was conducted from February 2018 to February 2020 after approval from the ethics review board of The University of Lahore, Lahore, Pakistan, and copmprised patients with mild to moderate strokewho were recruited from five public and two private hospitals of the Punjab province. Established guidelines were followed to translate the Stroke Impact Scale-16. The patients were concurrently evaluated on Barthel Index, Stroke Rehabilitation Assessment of Movement, Modified Rivermead Mobility Index, Modified Rankin Scale, Short Form 36 Health Survey Questionnaire and the Hospital Anxiety and Depression Scale to assess the validity of Stroke Impact Scale-16, and spearmen correlation coefficient was used to determine the correlation among the scales. Analysis of variance was employed to determine the discriminant validity. Intraclass correlation coefficient, weighted kappa, Cronbach’s alpha and item-total correlation were calculated to establish the stability and consistency of Stroke Impact Scale-16. Data was analysed using SPSS 25. Results: Of the 90 patients, 50(55.5%) were females and 40(45.5%) were males. The subjects were aged 50-80 years. The correlation of Stroke Impact Scale-16 was strong with the established tools and ranged from 0.78 to 0.91. The discriminant validity was also significant (p<.001) across all Modified Rankin Scale levels. The Intraclass correlation coefficient was 0.94 and Cronbach’s alpha was 0.91 for test-retest reliability and internal consistency, respectively. --Continue